PARTICIPATORY APPROACHES’ OPERATIONALIZATION ON SCALING-UP BLACK SOLDIER FLY LARVAE AS AN ALTERNATIVE PROTEIN SOURCE FOR LIVESTOCK FEED. A CROSS-SECTIONAL STUDY OF NKOZI SUB-COUNTY IN MPIGI DISTRICT. - Nansamba, Phionah; Nassimbwa, Florence (Student’s Journal of Health Research Africa, 2023)
Background: Demand for proteins has increased beyond supply due to the duo competition between humans and animals. Flora and fauna are depleted for proteins used in livestock feeds, this has raised production costs. Current protein insecurity can be solved by the black soldier fly larvae technology that uses organic waste to produce nutritive biomass rich in proteins. However, the innovation has not scaled up among farmers even though participatory approaches have always been employed to scale up different agricultural innovations. Methodology A cross-sectional study design with both qualitative and quantitative approaches was used with a sample of 397 respondents selected randomly and purposively among the livestock sector stakeholders. Results The animal sector has not effectively employed participatory approaches unlike the crop sector since most livestock farmers get extension and advisory services from radios and fellow farmers and share knowledge on innovations from farmer research groups and On-farm demonstrations which show a higher percentage of participatory approaches utilized by the farmers. Conclusion Effort is required to emphasize farmer research groups and On-farm demonstrations with the help of researchers, district veterinary officers, and Sub-County animal husbandry officers to scale up BSFL breeding among livestock farmers as an alternative protein for livestock feed. Recommendation The animal sector should streamline training and knowledge sharing of research findings to farmers instead of being only service providers i.e treating sick animals and selling drugs; more emphasis also should be put on training more animal scientists to bridge the gap between animal research scientists, Veterinary Officers, husbandry officers, and farmers to allow sharing of knowledge and diffusion of innovations like BSFL breeding using participatory approaches, the animal sector should put in place demonstration centers at both national and village level to allow farmers appreciate the innovation before taking it up.